Prevalence of Myocardial Infarction With Obstructive and Non-Obstructive Coronary Arteries in a Middle-Aged Population With Chronic Airflow Limitation: A Cross-Sectional Study - Sundh J; Ekström M; Blomberg A; Lindberg E; Malinovschi A; Olin AC; Sköld CM; Torén K; Wollmer P; Östgren CJ; Jernberg T (International Journal of COPD)
Josefin Sundh,1 Magnus Ekström,2 Anders Blomberg,3 Eva Lindberg,4 Andrei Malinovschi,5 Anna-Carin Olin,6 C Magnus Sköld,7,8 Kjell Torén,6 Per Wollmer,6 Carl Johan Östgren,9,10 Tomas Jernberg11,12 1Department of Respiratory Medicine, Faculty of Medicine and Health, Örebro University, Örebro, Sweden; 2Lund University, Faculty of Medicine, Department of Clinical Sciences Lund, Respiratory Medicine, Allergology and Palliative Medicine, Lund, Sweden; 3Department of Public Health and Clinical Medicine, Umeå University, Umeå, Sweden; 4Department of Medical Sciences, Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 5Department of Medical Sciences, Clinical Physiology, Uppsala University, Uppsala, Sweden; 6Occupational and Environmental Medicine, School of Public Health and Community Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 7Respiratory Medicine Unit, Department of Medicine Solna and Center for Molecular Medicine, Karolinska Institutet, Stockholm, Sweden; 8Department of Respiratory Medicine and Allergy, Karolinska University Hospital, Stockholm, Sweden; 9Department of Translational Medicine, Lund University, Malmö, Sweden; 10Centre of Medical Image Science and Visualization (CMIV), Linköping University, Linköping, Sweden; 11Department of Health, Medicine and Caring Sciences, Linköping University, Linköping, Sweden; 12Department of Clinical Sciences, Danderyd Hospital, Karolinska Institutet, Stockholm, SwedenCorrespondence: Josefin Sundh, Department of Respiratory Medicine, Faculty of Medicine and Health, Örebro University, Örebro, 701 82, Sweden, Tel +46702349517, Email josefin.sundh@regionorebrolan.se; josefin.sundh@oru.sePurpose: Myocardial infarctions (MIs) can occur in underlying obstructive coronary artery disease (MI-CAD) or in non-obstructive coronary arteries (MINOCA). The primary objectives of the study were to investigate the prevalence of MI-CAD and MINOCA in people with CAL, and to explore if CAL is an independent risk factor for MI-CAD and MINOCA. Secondary objectives were to explore these research questions stratified by sex and by smoking history.Patients and Methods: Cross-sectional analysis of the population-based Swedish CArdioPulmonary bioImage Study (SCAPIS) of people aged 50– 64 years. CAL was defined as a post-bronchodilator ratio of forced expiratory volume in one second and forced vital capacity below 0.70. MI-CAD was defined as a self-reported MI with coronary computed tomography angiography findings of previous revascularization or at least one significant coronary stenosis (> 50%), and MINOCA as self-reported MI with no previous revascularization and no significant coronary stenosis.Results: In total, 1735 (8.3%) of 20,882 included participants had CAL. MI-CAD was more common than MINOCA both in people with (2.8 vs 0.6%) and without CAL (1.2 vs 0.3%). Compared with those without CAL, people with CAL had an almost doubled independent risk of both MI-CAD ([adjusted OR] 1.72; [95% CI] 1.22– 2.42) and MINOCA (1.99; 1.02– 3.86). In men, CAL was associated with increased risk of MINOCA (2.63; 1.23– 5.64), and in women with increased risk for MI-CAD (3.43; 1.68– 1.26).Conclusion: Middle-aged people with CAL have an almost doubled risk of both MI-CAD and MINOCA, compared with people without CAL. In contrast to people without CAL, the risk of MINOCA is increased in men and the risk of MI-CAD is increased in women. In a clinical context, both MI types should be considered in CAL.Keywords: coronary atherosclerosis, COPD, smoking, sex